REPORT OF THE ANNUAL CONVENTION. - Cox, R. C. (The Accounting Review, 1957)
Abstract The 1956 annual meeting of the American Accounting Association offered an ideal opportunity to combine a first-class vacation trip with the meeting of friends and members of the association. It was held on August 27, 28, and 29, 1956, in Seattle, Washington, with the College of Business Administration, University of Washington, as hosts. The morning sessions of the convention program were devoted to the topics of faculty development and the tentative statement of cost concepts underlying reports for management purposes. Special activities included a boat trip across puget sound and a salmon bake held at Illahee State Park on Monday afternoon and evening. The association is greatly indebted to the committee on arrangements and the ladies program committee for the excellent facilities and arrangements made for them. A motion was made from the floor and carried accepting the report of the committee on nominations and instructing the secretary-treasurer to cast a unanimous ballot for election.